Development of a potent neutralizing nanobody against canine distemper virus hemagglutinin protein - Xiao, Lirong; Wu, Zhuqing; Su, Jingliang; Wu, Qingmin (Frontiers in Immunology, 2025)
Canine distemper virus (CDV) is the etiological agent of canine distemper. The virus can infect canids irrespective of age, sex, or breed, leading to a highly contagious and lethal disease that seriously threatens the health of canids, fur animals, and wildlife. Although vaccination can currently prevent CDV infection, developing effective emergency treatment drugs remains crucial. Nanobodies derived from camelid or shark heavy chain-only antibodies can effectively inhibit viral infections, suggesting their potential as therapeutic agents for treating CDV infection. In this study, we utilized a phage display nanobody library constructed from immunized alpacas and isolated a nanobody (Nb-6C6) that specifically binds to the CDV hemagglutinin (H) protein. Nb-6C6 was successfully expressed in mammalian cells and exhibited high binding affinity to CDV H (EC50 = 0.174 µg/mL). Neutralization assays further revealed that Nb-6C6 could effectively neutralize CDV (IC50 = 1.773 µg/mL). Fusion of Nb-6C6 with canine IgG Fc resulted in homodimers, significantly increasing its neutralizing activity by up to 4.6-fold. AlphaFold3 analysis indicated that the neutralizing capacity of Nb-6C6 against CDV is attributed to an interaction between residue D106 in the CDR3 region and the conserved residue R408 of the H protein. These findings suggest that the nanobody Nb-6C6 and its bivalent form exhibit high-affinity binding and potent neutralizing activity against CDV, highlighting their potential as promising therapeutic candidates for the treatment of CDV infection.